Furin-Triggered Peptide Self-Assembly Activates Coumarin Excimer Fluorescence for Precision Live-Cell Imaging - Peiyao Chen; Liling Meng; Yuting Wang; Xiaoya Yan; Meiqin Li; Yun Deng; Yao Sun (Molecules)
Monomer-to-excimer transition has become a valuable technique in fluorescence imaging because of its ability to enhance imaging contrast. However, from a practical perspective, the accuracy of excimer formation at target sites warrants further exploration. Enzyme-triggered peptide self-assembly provides a promising solution to this limitation. As a proof-of-concept, in this study, we developed a furin-triggered peptide self-assembling fluorescent probe RF-Cou by coupling a coumarin dye 7-(diethylamino)-2-oxo-2H-chromene-3-carboxylic acid (Cou) with a furin-responsive peptide scaffold for precision live-cell imaging. Upon entering furin-overexpressing 4T1 tumor cells, RF-Cou underwent enzymatic cleavage, releasing an amphiphilic peptide motif and self-assembling into nanoparticles largely concentrated in the Golgi apparatus to confine the diffusion of Cou. During this process, the Cou excimers were formed and induced a red shift in the fluorescence emission, validating the feasibility of RF-Cou in efficient excimer imaging of furin-overexpressing tumor cells. We expect that our findings will highlight the potential of stimuli-responsive small molecular peptide probes to advance excimer-based imaging platforms, particularly for enzyme-specific cell imaging and therapeutic monitoring.